2022
DOI: 10.3390/antibiotics11111659
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Bacteriophage Cocktail Active against Shigella Species and Testing of Its Therapeutic Potential in Galleria mellonella

Abstract: Shigellosis is a leading global cause of diarrheal disease and travelers’ diarrhea now being complicated by the dissemination of antibiotic resistance, necessitating the development of alternative antibacterials such as therapeutic bacteriophages (phages). Phages with lytic activity against Shigella strains were isolated from sewage. The genomes of 32 phages were sequenced, and based on genomic comparisons belong to seven taxonomic genera: Teetrevirus, Teseptimavirus, Kayfunavirus, Tequatrovirus, Mooglevirus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Our results support linear use of phages in therapy, as recently advocated by the Turner lab [12], instead of simultaneous application in cocktails to limit the likelihood of stress inductions of possibly pathogenic temperate phages. Simultaneous use of phages in cocktails is still considered state of the art [13,14]. Our findings may be useful to inform therapeutic approaches of our clinical partners [12][13][14], and the Phage4_1Health program [15].…”
Section: Introduction -Results -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support linear use of phages in therapy, as recently advocated by the Turner lab [12], instead of simultaneous application in cocktails to limit the likelihood of stress inductions of possibly pathogenic temperate phages. Simultaneous use of phages in cocktails is still considered state of the art [13,14]. Our findings may be useful to inform therapeutic approaches of our clinical partners [12][13][14], and the Phage4_1Health program [15].…”
Section: Introduction -Results -Discussionmentioning
confidence: 99%
“…Simultaneous use of phages in cocktails is still considered state of the art [13,14]. Our findings may be useful to inform therapeutic approaches of our clinical partners [12][13][14], and the Phage4_1Health program [15]. ( 903)…”
Section: Introduction -Results -Discussionmentioning
confidence: 99%
“…For instance, Rai et al ( 2022) [39] demonstrated the isolation of phages targeting methicillin-resistant S. aureus from sewage, while Sjahriani et al (2021) [40] reported a high abundance of phages against E. coli in environmental sewage. Additionally, Klai (2020) [41] noted that phages are prevalent in hospital waste, and research has shown their presence in wastewater treatment plants [42].…”
Section: Marrs Et Al (2021)mentioning
confidence: 99%
“…G. mellonella is a robust model organism that has gained popularity in recent decades. This model organism has been used for a wide range of assays including virulence assays (bacterial and fungal), immunotoxicity testing (concerning the adaptive immune system), drug toxicity assays, testing the effects of ultraviolet radiation, probiotics, and bacteriophage treatment efficacy (Cunha et al ., 2023, Stempinski, Smith and Casadevall 2022, Erbas et al ., 2023, Demirtürk, Uçkan, and Mert, 2023, Sabockyte et al ., 2023, Filippov et al ., 2022, Maslova et al ., 2023). G. mellonella are affordable, have low ethical considerations associated with their use and have low maintenance and handling requirements which could facilitate faster early-stage pathogen dissemination and prevention strategy testing.…”
Section: Introductionmentioning
confidence: 99%